2003
DOI: 10.1017/s0022336000043444
|View full text |Cite
|
Sign up to set email alerts
|

Uppermost Cambrian-lower Ordovician faunas and Laurentian platform sequence stratigraphy, eastern New York and Vermont

Abstract: The Cambrian–Ordovician boundary is a type 1 depositional sequence boundary with dramatic local erosional incision in restricted marine facies on the easternmost New York Promontory. The systemic boundary is bracketed below by Late Cambrian, upper Cordylodus proavus Zone (s.s). conodonts from carbonates of the upper Little Falls Formation (=Whitehall Formation, abandoned). Presumed Lower Ordovician ellesmeraceratoid cephalopods from the upper Little Falls are uppermost Cambrian and among the oldest known in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(101 citation statements)
references
References 37 publications
1
100
0
Order By: Relevance
“…The Rochdale Formation is one of the least areally extensive formations of the Beekmantown Group in this region. Landing & Westrop (2006;also Landing, 2002;Landing, Westrop & Van Aller Hernick, 2003;Landing, Westrop & Keppie, 2007) determined that the Tribes Hill Formation, the lowest Ordovician unit of the Beekmantown Group, was deposited during a eustatic high that submerged Laurentia as far as Wisconsin and Minnesota in late early Tremadocian times. However, the next overlying Beekmantown Group formation is a depositional sequence that records a late Tremadocian eustatic high that did not lead to transgression west of the roughly N-S line defined by the modern Hudson River-Lake Champlain lowlands (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Rochdale Formation is one of the least areally extensive formations of the Beekmantown Group in this region. Landing & Westrop (2006;also Landing, 2002;Landing, Westrop & Van Aller Hernick, 2003;Landing, Westrop & Keppie, 2007) determined that the Tribes Hill Formation, the lowest Ordovician unit of the Beekmantown Group, was deposited during a eustatic high that submerged Laurentia as far as Wisconsin and Minnesota in late early Tremadocian times. However, the next overlying Beekmantown Group formation is a depositional sequence that records a late Tremadocian eustatic high that did not lead to transgression west of the roughly N-S line defined by the modern Hudson River-Lake Champlain lowlands (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Ulrich et al (1944) reported the proterocamerocerid Cotteroceras Ulrich et al 1944, from the Roubidoux Formation in the Ozark region of Missouri. The Roubidoux spans the Low Diversity Interval-Macerodus dianae Zone (conodonts) and is approximately timeequivalent with the Rochdale Formation (Repetski, Loch & Ethington, 1998;Landing, Westrop & Van Aller Hernick, 2003). The Longview Limestone of Virginia from which Ulrich et al (1944, p. 16) reported a number of pilocerids and proterocamerocerids is probably time-equivalent to the Rochdale Formation.…”
Section: A Origin Of the Endoceridamentioning
confidence: 99%
See 1 more Smart Citation
“…Development of a strongly dysoxic mid-water mass on continental slopes is recorded during this interval (middle-late part of the early Tremadoc) of high eustatic levels (Landing, Benus & Whitney, 1992;Landing, Westrop & van Aller Hernick, 2003), and an onlap of this low-oxygen water is apparently recorded by the lower Río Salinas Member.…”
Section: C Depositional History Of Río Salinas Membermentioning
confidence: 83%
“…This sea-level rise is apparently eustatic, as it correlates with sea-level rise within the Rossodus manitouensis Chron that drove shorelines into the upper Mississippi River valley region in Laurentia (Landing, Benus & Whitney, 1992;Ross & Ross, 1995;Landing, Westrop & van Aller Hernick, 2003;Landing & Westrop, 2006) and across Baltica during the 'early to middle Tremadoc highstand interval' (Nielsen, 2004). Development of a strongly dysoxic mid-water mass on continental slopes is recorded during this interval (middle-late part of the early Tremadoc) of high eustatic levels (Landing, Benus & Whitney, 1992;Landing, Westrop & van Aller Hernick, 2003), and an onlap of this low-oxygen water is apparently recorded by the lower Río Salinas Member.…”
Section: C Depositional History Of Río Salinas Membermentioning
confidence: 99%